Risk Management Analysis of Sharia Gold Pawn Financing Products at BPRS Bhakti Sumekar - Taufik Aris Saputra (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
BPRS Bhakti Sumekar Bandaran, Tlanakan Sub-Branch Office offers various products needed by the community such as financing products, funding products, and service products. One of the financing products available at the BPRS Bhakti Sumekar is iB Maslahah’s Gold Partner a gold-backed qardh product in which the bank provides financing facilities to customers with gold collateral. The study aims to determine what are the risks experienced by financing gold pawning products and how the risk management process is carried out by BPRS Bhakti Sumekar in Sharia gold pawning financing products. This research is a type of qualitative research using a descriptive approach. Data was obtained by interview, observation, and documentation. Data credibility test uses triangulation data credibility test. While data analysis techniques use: Data reduction, data presentation, and drawing conclusions. Thus, based on the analysis of Sharia gold pawning financing risk at BPRS Bhakti Sumekar Bandaran, Tlanakan the highest risk is market risk, operational risk, and strategic risk. While compliance risk, legal risk, credit risk, reputation risk, and liquidity risk have low risks.